2020
DOI: 10.3389/fcomm.2020.00069
|View full text |Cite
|
Sign up to set email alerts
|

Ninety Minutes to Reduce One's Intention to Eat Meat: A Preliminary Experimental Investigation on the Effect of Watching the Cowspiracy Documentary on Intention to Reduce Meat Consumption

Abstract: Whereas, past research has shown that using environmental arguments to reduce meat intake are unsuccessful in awareness campaigns, popular documentaries might have the potential to successfully change the public awareness of the environmental implications of meat consumption today. This preliminary study aimed to provide first empirical evidence of the potential effects of watching a popular documentary on a less-known environmental topic among a population that are habitual performers of the behavior under di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…Documentaries such as ‘The Game Changers’ which promoted the potential benefits of a vegetarian‐based diet for athletes and attracted extensive media attention (Vitale & Hueglin, 2021 ) may be driving this shift. Similarly, popular documentaries such as ‘Cowspiracy’ outlining the environmental impact of meat production can have a substantial influence on consumer behaviour which may shape changes in vegetarian‐based dietary motives in both athletes and non‐athletes (Pabian et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Documentaries such as ‘The Game Changers’ which promoted the potential benefits of a vegetarian‐based diet for athletes and attracted extensive media attention (Vitale & Hueglin, 2021 ) may be driving this shift. Similarly, popular documentaries such as ‘Cowspiracy’ outlining the environmental impact of meat production can have a substantial influence on consumer behaviour which may shape changes in vegetarian‐based dietary motives in both athletes and non‐athletes (Pabian et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggested significant behaviour change can result through popular streaming programs, such as ‘What the Health’, which was the most popular streaming content reported by participants in the present study. Such programs have been criticised for having distinctive viewpoints, misreporting evidence, and cherry-picking studies [ 37 , 38 ]. Given the compelling way healthy lifestyle content can be presented and the global reach and exposure they have, the implications of this platform warrant further attention.…”
Section: Discussionmentioning
confidence: 99%
“…There are signs that documentaries and other animal imagery can have positive impacts on viewers (Beattie et al., 2011; Males & Van Aelst, 2021; Thomas‐Walters et al., 2020). Studies have shown that viewing Cowspiracy can reduce ones intentions to eat meat (Pabian et al., 2020). In one study, Blue Planet II was found to increase knowledge, but it did not translate into a willingness to pay to change the status quo (Hynes et al., 2021) or change viewers actual behaviours (Dunn et al., 2020).…”
Section: Introductionmentioning
confidence: 99%